Diversivikasi Pengolahan Ikan Asap Menjadi Produk Makanan Siap Saji Pada Kelompok Usaha Pengasapan Ikan Di Tanjung Qencono Kecamatan Way Bungur, Kabupaten Lampung Timur - Iswati Iswati; Noval Sahnitri; Vastika Yulia Putri; Syifana Zakia Zulfa; Nadya Pramudita (Universitas 45 Surabaya, 2024)
This Community Service Activity is focused on assisting fish smoking business groups in producing a product that can be consumed and utilized by the community. Based on field observations, it was found that not many people know the process of making processed smoked fish. From the results of the audience with fish smoking businesses, so far they only know that broomstick fish is a fish that cannot be consumed and is made into a variety of processed foods. But with the knowledge approach that with good and correct processing, it turns out that other types of broomstick fish, apart from being smoked, can also be processed, for example into smoked fish with balado spices, shredded meatballs, meatballs, etc., and unexpectedly the response from the participants was very positive and they were even enthusiastic to try it. The aim of this activity is to provide knowledge or education to mothers, especially smoked fish business actors, to make innovations in the businesses they are engaged in with the aim of increasing consumer interest in their products and having an effect on improving the economic conditions of these business actors.